First luminescent material and luminescent material composition comprising same and organic electroluminescent device
Patent Information
- Application Number
- CN202611143793.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-30
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2046-07-30
AI Technical Summary
现有技术中,蒽基主体材料在激发态下,未氘代的蒽环上活泼氢易与相邻基团发生环化反应,生成光降解杂质,形成激子猝灭陷阱,导致发光效率下降、器件寿命缩短
本发明提供了一种用于有机电致发光器件的第一发光材料,该第一发光材料通过选择性氘代与分子间距调控的协同策略,可有效抑制光化学降解、维持载流子平衡并优化分子间堆积。
Smart Images

Figure CN122685559B_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of OLED technology, specifically including a first luminescent material, a luminescent material composition containing the same, and an organic electroluminescent device. Background Technology
[0002] In the field of organic light-emitting diodes (OLEDs), the stability and carrier balance of the host material in the emitting layer have a decisive impact on device efficiency and lifetime. In existing technologies, in the excited state, the active hydrogen on the undeuterated anthracene ring of the anthracene host material easily undergoes cyclization reactions with adjacent groups, generating photodegradation impurities and forming exciton quenching traps, leading to decreased luminous efficiency and shortened device lifetime. Although full deuteration can suppress photodegradation, excessive deuteration (especially for p-type carbazole groups) significantly alters carrier mobility, resulting in excessive hole transport capacity, disrupting the electron-hole balance, exacerbating polaron-exciton quenching, and consequently reducing external quantum efficiency (EQE) and causing severe efficiency roll-off. Therefore, how to suppress photodegradation while maintaining carrier balance, controlling intermolecular spacing, and synergistically improving device efficiency and lifetime is a pressing technical challenge that needs to be addressed. Summary of the Invention
[0003] In view of the above-mentioned problems existing in the prior art, the present invention provides a first luminescent material, a luminescent material composition containing the same, and an organic electroluminescent device.
[0004] To achieve the above objectives, the technical solution adopted by the present invention includes: A first aspect of the present invention provides a first luminescent material, the general structural formula of which is shown below: I; Ar is selected from deuterated monocyclic aromatic hydrocarbons or polycyclic aromatic hydrocarbons with C6 to C30 carbon atoms; L1 is selected from monocyclic aromatic hydrocarbons or polycyclic aromatic hydrocarbons with single bonds and deuterated carbon atoms, having a carbon number of C6 to C30. L2 is selected from phenyl groups substituted with R or naphthyl groups substituted with R, where R represents a monosubstituted group to the most permissible substituent, each independently selected from any one of deuterated, deuterated or non-deuterated phenyl groups, or deuterated or non-deuterated naphthyl groups.
[0005] Furthermore, Ar is selected from deuterated monocyclic aromatic hydrocarbons or polycyclic aromatic hydrocarbons with 6 to 20 carbon atoms; L1 is selected from monocyclic aromatic hydrocarbons or fused-ring aromatic hydrocarbons with single bonds and deuterated carbon atoms, ranging from C6 to C20.
[0006] Furthermore, the Ar is selected from any one of deuterated phenyl, deuterated naphthyl, deuterated phenanthryl, deuterated pyrene, and deuterated benzanthracene. The L1 is selected from any one of single bond, deuterated phenyl, deuterated naphthyl, deuterated phenanthryl, and deuterated pyrene.
[0007] Furthermore, L2 is selected from , , , , , , , , , , , , , , , , , , , , , Any one of them.
[0008] Furthermore, the first luminescent material is selected from the structure shown below:
[0009]
[0010]
[0011]
[0012]
[0013]
[0014]
[0015]
[0016]
[0017]
[0018]
[0019]
[0020]
[0021]
[0022]
[0023]
[0024]
[0025]
[0026]
[0027] .
[0028] A second aspect of the present invention provides a luminescent material composition comprising a first luminescent material as described above and a second luminescent material having the following general structural formula; II; Wherein, X represents any one of substituted or unsubstituted phenyl, substituted or unsubstituted naphthyl, substituted or unsubstituted phenanthryl, or substituted or unsubstituted pyrene, and when X contains a substituent, the substituent is selected from phenyl or naphthyl. Y represents any one of phenyl, biphenyl, terphenyl, or naphthyl; In Formula II, any one of the hydrogen atoms can be replaced by deuterium.
[0029] Furthermore, the second luminescent material is selected from the structure shown below:
[0030]
[0031]
[0032]
[0033]
[0034]
[0035] .
[0036] A third aspect of the invention provides the use of the first luminescent material as described above or the luminescent material composition as described above in the preparation of organic electroluminescent devices.
[0037] A fourth aspect of the present invention provides an organic electroluminescent device comprising an anode, a hole transport region, a light-emitting layer, an electron transport region, and a cathode sequentially disposed on a substrate; wherein the light-emitting layer comprises a first light-emitting material as shown in Formula I above.
[0038] Furthermore, the light-emitting layer includes a host material and a guest material, wherein the host material is selected from the first light-emitting material shown in Formula I as described above.
[0039] A fifth aspect of the present invention provides an organic electroluminescent device comprising an anode, a hole transport region, a light-emitting layer, an electron transport region, and a cathode sequentially disposed on a substrate; wherein the light-emitting layer comprises a light-emitting material composition as described above.
[0040] Furthermore, the light-emitting layer includes a host material and a guest material. The host material is selected from the light-emitting material composition described above, that is, the light-emitting layer of the organic electroluminescent device contains a combination of a first light-emitting material and a second light-emitting material as the host material.
[0041] Beneficial effects of this invention: This invention provides a first luminescent material for organic electroluminescent devices. This first luminescent material can effectively suppress photochemical degradation, maintain carrier balance and optimize intermolecular stacking through a synergistic strategy of selective deuteration and intermolecular spacing regulation.
[0042] Selective deuteration refers to deuterating the parent anthracene core and the L1, L2, and Ar segments connected to the parent anthracene core in the first luminescent material provided by this invention, without deuterating the carbazole fragment in the first luminescent material. By deuterating the parent anthracene core and the L1, L2, and Ar segments connected to the parent anthracene core in the first luminescent material, this invention can slow down the photodegradation rate in the excited state, effectively suppress the generation of non-radiative recombination centers and non-radiative decay channels, thereby improving the intrinsic operational stability of the device. By limiting the deuteration of the carbazole fragment in the first luminescent material, this invention can avoid carrier transport bias towards the P-type, thus preventing carrier transport imbalance.
[0043] Intermolecular distance regulation refers to the specific restriction of the structures of L2 and Ar. By adding steric hindrance groups with specific structures between carbazole and anthracene-based cores and by specifically restricting the structure of Ar, it is possible to maintain a high hole transport rate in the material while avoiding carrier imbalance, so that excitons can recombine effectively under a relatively balanced carrier transport.
[0044] Therefore, by differentially controlling the degree of deuteration of the first luminescent material (i.e., the carbazole group is not deuterated while other groups are deuterated), the present invention specifically defines the structure of L2 and Ar. This not only slows down the photodegradation rate in the excited state and improves the stability of the material, but also avoids carrier imbalance while maintaining the high hole transport rate of the material, thereby achieving a good match between holes and electrons, reducing exciton quenching, and improving exciton utilization, thus achieving high external quantum efficiency (EQE) and long lifetime (LT) of the device.
[0045] This invention also combines the first luminescent material with the second luminescent material shown in Formula II, which can further improve the efficiency and lifetime of the device. Specifically, the composition provided by this invention can better control the intermolecular spacing and carrier balance. Through the interaction of the composition provided by this invention, the overall deuteration rate of the luminescent layer can be increased, thereby improving the device lifetime. This avoids the dilemma that while deuteration of carbazole groups can improve lifetime, it also promotes hole transport, which is detrimental to carrier balance. Attached Figure Description
[0046] Figure 1 This is a schematic diagram of the structure of the organic electroluminescent device of the present invention, wherein 1-substrate, 2-anode, 3-hole injection layer, 4-hole transport layer, 5-light-emitting auxiliary layer, 6-light-emitting layer, 7-hole blocking layer, 8-electron transport layer, 9-electron injection layer, 10-cathode, and 11-capping layer. Detailed Implementation
[0047] To better understand the content of this invention, it will be described in detail with reference to the accompanying drawings and embodiments.
[0048] The compounds of this invention are applicable to light-emitting elements, display panels, and electronic devices, particularly organic electroluminescent devices. The electronic devices described in this invention are devices comprising a layer containing at least one first light-emitting material, and may also comprise layers formed entirely of inorganic materials or inorganic materials. Preferably, the electronic devices are organic electroluminescent devices (OLEDs), organic integrated circuits (O-ICs), organic field-effect transistors (O-FETs), organic thin-film transistors (O-TFTs), organic light-emitting transistors (O-LETs), organic solar cells (O-SCs), organic dye-sensitized solar cells (O-DSSCs), organic optical detectors, organic photosensors, organic field quenching devices (O-FQDs), light-emitting electrochemical cells (LECs), organic laser diodes (O-lasers), and organic plasma emitting devices. Organic electroluminescent devices (OLEDs) are particularly preferred. A schematic diagram of an exemplary organic electroluminescent device is shown below. Figure 1 As shown.
[0049] Experimental Section To better understand the content of this invention, the polycyclic compound, the preparation method of the compound, and the luminescent properties of the device will be explained in detail with reference to embodiments. Various chemical reactions can be applied to the synthesis method of the compound according to one embodiment of this invention. However, it should be noted that the synthesis method of the compound according to one embodiment of this invention is not limited to the synthesis method described below. Unless otherwise stated, subsequent synthesis is carried out in an anhydrous solvent under a protective gas atmosphere. Solvents and reagents can be purchased from conventional reagent suppliers.
[0050] Synthesis of intermediates for the first luminescent material
[0051] Compound K-1 (16.7 g, 0.1 mol), compound L-1 (31.13 g, 0.1 mol), and potassium hydroxide (5.6 g, 0.1 mol) were dissolved in 500 mL of dimethylformamide, and the mixture was heated to 80 °C and stirred for 6 hours. After the reaction was completed, the mixture was allowed to cool naturally to room temperature, and the system was added to 1000 mL of purified water. A solid precipitated, and the crude product was collected by filtration. The resulting filter cake was recrystallized twice from a mixture of toluene and ethanol (volume ratio 1:3) to obtain the target compound Sub-1 (34.84 g, 0.076 mol), with a yield of 76%. The mass spectrometry characterization result was MS (m / z) (M+H): 459.48.
[0052] Compound Sub-1 (34.84 g, 0.076 mol) was dissolved in 250 mL of anhydrous tetrahydrofuran and cooled to -78 °C. A solution of n-butyllithium in n-hexane (2.5 mol / L, 40 mL, 0.101 mol) was slowly added dropwise with stirring. After the addition was complete, the reaction mixture was maintained at -78 °C for 1 hour. Trimethyl borate (8.32 g, 0.08 mol) was added to the system, and stirring continued for 30 minutes. The reaction mixture was heated to 0 °C, and 100 mL of 1 mol / L hydrochloric acid was added. The mixture was then allowed to warm naturally to room temperature and stirred for 1 hour. 500 mL of toluene and 500 mL of water were added to the reaction mixture. The mixture was separated, and the organic phase was concentrated under reduced pressure to obtain the crude product. The crude product was purified by silica gel column chromatography (petroleum ether / ethyl acetate = 1:1, v / v) to give the target compound A1 (23.28 g, 0.055 mol), with a yield of 73%. MS(m / z)(M+H): 424.28.
[0053] Other first-light-emitting material intermediates can be prepared using a preparation method similar to that of A1.
[0054] Synthesis Example 1
[0055] Compounds Z1 (3.46 g, 10 mmol) and A1 (4.23 g, 10 mmol) were placed in 100 mL of a toluene / water / ethanol mixture (volume ratio 4:1:1). Potassium carbonate (1.65 g, 10 mmol) and 1,1'-bis(diphenylphosphine)ferrocene palladium dichloride (Pd(dppf)Cl2, 73 mg, 0.1 mmol) were added under nitrogen atmosphere. The reaction mixture was heated to reflux and stirred for 12 hours. After the reaction was complete, it was cooled to room temperature and then quenched by pouring the mixture into ice water. The organic phase was extracted by liquid-liquid extraction, dried over anhydrous magnesium sulfate, filtered, and the solvent was removed under reduced pressure to obtain the crude product. The crude product was purified by column chromatography to give the target compound BH1 (5.67 g, yield 88%). MS (m / z) (M+H): 645.78.
[0056] Synthesis Example 2 This synthetic example provides a method for preparing compound BH2. The synthetic route of this compound is as follows:
[0057] The preparation method was the same as in Example 1, except that compound A2 (2.91 g; 10 mmol) replaced compound A1 and compound Z4 (4.25 g; 10 mmol) replaced compound Z1. The final product BH2 was 4.85 g, yield: 82%, MS (m / z)(M+H): 592.48.
[0058] Synthesis Example 3 This synthetic example provides a method for preparing compound BH3. The synthetic route of this compound is as follows:
[0059] The preparation method was the same as in Example 1, except that compound A3 (2.91 g; 10 mmol) replaced compound A1 and compound Z3 (3.97 g; 10 mmol) replaced compound Z1, and the final product BH3 was 4.11 g, yield: 73%, MS (m / z)(M+H): 564.47.
[0060] Synthesis Example 4 This synthetic example provides a method for preparing compound BH4. The synthetic route of this compound is as follows:
[0061] The preparation method was the same as in Example 1, except that compound A4 (4.16 g; 10 mmol) replaced compound A1 and compound Z5 (5.29 g; 10 mmol) replaced compound Z1. The final product was BH4: 6.31 g, yield: 77%, MS (m / z) (M+H): 821.58.
[0062] Synthesis Example 5 This synthetic example provides a method for preparing compound BH5. The synthetic route of this compound is as follows:
[0063] The preparation method was the same as in Example 1, except that compound A5 (4.13 g; 10 mmol) replaced compound A1 and compound Z13 (4.90 g; 10 mmol) replaced compound Z1. The final product was BH5: 5.68 g, yield: 73%, MS (m / z)(M+H): 779.92.
[0064] Synthesis Example 6 This synthetic example provides a method for preparing compound BH6. The synthetic route of this compound is as follows:
[0065] The preparation method was the same as in Example 1, except that compound B1 (4.18 g; 10 mmol) replaced compound A1 and compound Z12 (4.77 g; 10 mmol) replaced compound Z1. The final product was BH6: 6.08 g, yield: 79%, MS (m / z) (M+H): 771.56.
[0066] Synthesis Example 7 This synthetic example provides a method for preparing compound BH7. The synthetic route of this compound is as follows:
[0067] The preparation method was the same as in Example 1, except that compound B2 (4.18 g; 10 mmol) replaced compound A1 and compound Z6 (4.49 g; 10 mmol) replaced compound Z1, and the final product BH7 was obtained: 6.53 g, yield: 88%, MS (m / z)(M+H): 743.54.
[0068] Synthesis Example 8 This synthetic example provides a method for preparing compound BH8. The synthetic route of this compound is as follows:
[0069] The preparation method was the same as in Example 1, except that compound B3 (3.43 g; 10 mmol) was used to replace compound A1, and the final product BH8 was obtained: 4.79 g, yield: 85%, MS (m / z) (M+H): 564.49.
[0070] Synthesis Example 9 This synthetic example provides a method for preparing compound BH9. The synthetic route of this compound is as follows:
[0071] The preparation method was the same as in Example 1, except that compound B4 (3.43 g; 10 mmol) replaced compound A1 and compound Z8 (4.77 g; 10 mmol) replaced compound Z1. The final product was BH9: 5.98 g, yield: 86%, MS (m / z)(M+H): 696.54.
[0072] 1 H NMR (400 MHz, Chloroform- d ) δ 8.22 (d, J = 7.8 Hz, 2H), 7.69 (d, J =8.2 Hz, 2H), 7.52 (t, J = 7.7 Hz, 2H), 7.37 (t, J = 7.4 Hz, 2H). Synthesis Example 10 This synthetic example provides a method for preparing compound BH10. The synthetic route of this compound is as follows:
[0073] The preparation method was the same as in Example 1, except that compound B5 (4.18 g; 10 mmol) replaced compound A1 and compound Z9 (5.01 g; 10 mmol) replaced compound Z1. The final product was BH10: 4.92 g, yield: 62%, MS (m / z)(M+H): 795.56.
[0074] Example 11 This synthetic example provides a method for preparing compound BH11. The synthetic route of this compound is as follows:
[0075] The preparation method was the same as in Example 1, except that compound C1 (3.66 g; 10 mmol) replaced compound A1 and compound Z2 (3.97 g; 10 mmol) replaced compound Z1. The final product was BH11: 4.40 g, yield: 69%, MS (m / z) (M+H): 639.49.
[0076] Synthesis Example 12 This synthetic example provides a method for preparing compound BH12. The synthetic route of this compound is as follows:
[0077] The preparation method was the same as in Example 1, except that compound C2 (3.66 g; 10 mmol) replaced compound A1 and compound Z10 (4.73 g; 10 mmol) replaced compound Z1, and the final product BH12 was obtained: 6.07 g, yield: 85%, MS (m / z) (M+H): 715.50.
[0078] Synthesis Example 13 This synthetic example provides a method for preparing compound BH13. The synthetic route of this compound is as follows:
[0079] The preparation method was the same as in Example 1, except that compound C3 (3.66 g; 10 mmol) replaced compound A1 and compound Z7 (4.73 g; 10 mmol) replaced compound Z1, and the final product BH13 was obtained: 5.57 g, yield: 78%, MS (m / z)(M+H): 715.5.
[0080] Synthesis Example 14 This synthetic example provides a method for preparing compound BH14. The synthetic route of this compound is as follows:
[0081] The preparation method was the same as in Example 1, except that compound C4 (3.66 g; 10 mmol) replaced compound A1 and compound Z11 (4.49 g; 10 mmol) replaced compound Z1, and the final product BH14 was obtained: 4.55 g, yield: 66%, MS (m / z)(M+H): 691.5.
[0082] Synthesis Example 15 This synthetic example provides a method for preparing compound BH15. The synthetic route of this compound is as follows:
[0083] The preparation method was the same as in Example 1, except that compound C5 (4.41 g; 10 mmol) was replaced with compound A1, and the final product BH15 was obtained: 4.69 g, yield: 71%, MS (m / z) (M+H): 662.49.
[0084] Second luminescent material The following are several secondary luminescent materials, with their specific structures as follows: .
[0085] Composition Examples Compositions T1 to T6 are obtained by combining the first luminescent material and the second luminescent material according to Table 1 and mixing them evenly, wherein the mass ratio of the first luminescent material to the second luminescent material is 50:50.
[0086] Table 1
[0087] Comparative compounds The following are several compounds, DBH1 to DBH8, that were tested during the research process. They form a contrasting structure with the first luminescent material of this invention, and their specific structural formulas are shown below: .
[0088] The following are several luminescent materials, DBHB1 to DBHB4, that were tested during the research process. They form a contrasting structure with the second luminescent material of this invention, and their specific structural formulas are shown below: .
[0089] Comparative examples of compositions Compositions DT1 to DT4 are obtained by combining the luminescent materials according to Table 2 and mixing them evenly.
[0090] Table 2
[0091] Compound performance evaluation To illustrate the advantages of the compounds of the present invention, the following experiments were conducted: 1. Photoluminescence (PL) Intensity Retention Rate: To evaluate the degradation rate, compounds BH1 to BH15 and DBH1 to DBH8 were deposited into films by vapor deposition, and the photostability of the films under 254 nm UV irradiation was measured. The PL photoluminescence (PL) intensity of the film samples was measured using a Jasco FP-6500 fluorescence spectrophotometer under a nitrogen atmosphere. The PL intensity of the samples after 48 hours of irradiation was compared with the PL intensity under initial conditions. The PL intensity retention rate results are shown in Table 3. A higher retention rate indicates less photodegradation and greater stability of the material in the excited state, which is beneficial for extending device lifetime.
[0092] 2. Intermolecular average distance (R_BH): Using Gromacs 2019.3 software, a 10*10*10nm cubic box was constructed based on the GAFF force field and RESP atomic charge. The host molecules were randomly placed into this box using the conjugate gradient method, minimizing energy to eliminate the repulsive forces caused by unreasonable intermolecular arrangement in the system. Then, a 100ps equilibrium molecular MD simulation was performed under NVT to bring the system to complete equilibrium. Based on this system, a 5ns generation MD simulation was performed using NPT with periodic boundary conditions under an external environment setting of 1 atm and 298K. The MD trajectory of the last 2ns was divided into 20 parts, and the intermolecular average distance (R_BH) between the two host compounds in this invention was calculated. The results are shown in Table 3.
[0093] The host and guest molecular structures used in the MD simulations were obtained using Gaussian 16 C.01 software, based on density functional theory (DFT) calculations (basis set level set to b3lyp / 6-31G(d), charge number 0), through geometric optimization and vibrational analysis (Opt+freq). During the calculations, none of the structures used had imaginary frequencies.
[0094] 3. Mobility: To demonstrate that the first luminescent material provided by this invention can balance carrier transport, the hole mobility μh and electron mobility μe of compounds BH1 to BH15 and compounds DBH1 to DBH8 were measured, and then μh / μe was calculated. The closer the value of μh / μe is to 1, the more balanced the carrier transport in the compound is. The larger the value, the stronger the hole transport capability.
[0095] Time-of-flight (TOF) experiments are currently the most effective method for measuring carrier mobility in organic semiconductor materials. They can test the relatively low mobilities of small organic molecules and polymers that can be fabricated into thin films, as well as the low mobilities of crystalline materials. The TOF experiment utilizes the photoconductivity of organic semiconductor materials. It measures the time it takes for photogenerated carriers to travel through the sample under an applied electric field, and then calculates the carrier mobility based on the relationship between the mobility, the external electric field, and the carrier drift velocity. The applied deflection voltage is V, the time it takes for holes or electrons to travel through the thin-film device is t, the film thickness is d, and the formula for calculating the mobility μh or μe is: μ = d. 2 / Vt. Specific experimental steps: ① The compounds BH1 to BH15 and the comparative compounds DBH1 to DBH8 provided by the present invention were deposited on ITO to form a 1000 nm thin film, and then (Al) was deposited on the thin film to form a cathode with a thickness of 150 nm to prepare the sample to be tested. ② Apply a 20V deflection voltage to the sample under test. Measure the time it takes for photogenerated carriers to travel through the sample under the applied electric field, and calculate the hole mobility μh and electron mobility μe of the material. Further calculate μh / μe. The closer the μh / μe value is to 1, the more balanced the carrier transport. The specific calculation results are shown in Table 3.
[0096] Table 3
[0097] As shown in Table 3, compared with the comparative compounds, the compounds provided by the present invention have a higher PL intensity retention rate, a larger average distance between R_BH molecules, and a more balanced carrier transport, which can achieve a good match between holes and electrons and improve exciton utilization.
[0098] Table 3 shows the PL intensity retention rate data. It can be seen that when the anthracene core or the hydrogen adjacent to the anthracene core in the first luminescent material is not deuterated, photochemical side reactions occur, generating ring-closing impurities, which affect the PL intensity. The deeper the impact of the side reactions, the lower the PL intensity retention rate. In comparison compound DBH8, the anthracene core and the groups on both sides of the anthracene core are completely undeuterated, resulting in the deepest impact from photochemical side reactions, the most photodegradation impurities, and the lowest PL retention rate. In comparison compounds DBH3 and DBH7, only the groups on one side of the anthracene core are deuterated; the active sites of the anthracene core will undergo ring-closing side reactions with the groups on the other side, generating ring-closing impurities and affecting the luminescence intensity. In comparison compound DBH2, only the anthracene core is deuterated, and in compound DBH4, only the groups on both sides of the anthracene core are deuterated; the corresponding active hydrogens still undergo side reactions, but the impact is less severe. In comparison compounds DBH1 and DBH5, the flanking groups of the anthracene core contain active hydrogens; although the situation is better than other comparative compounds, the influence of photochemical side reactions cannot be avoided. In contrast, compound DBH6 is entirely deuterated, lacking active hydrogen, resulting in stable luminescence intensity that is almost unaffected by photochemical side reactions. This invention, by deuterating the anthracene core of the first luminescent material, as well as L1, L2, and Ar connected to the core, can slow down the photodegradation rate in the excited state and effectively suppress the formation of non-radiative recombination centers and non-radiative decay channels. Therefore, it is less affected by photochemical side reactions and has a relatively high PL retention rate.
[0099] Regarding carrier balance, since deuteration affects vibrational frequencies and reduces molecular skeleton vibrations, the deuteration strategy enhances the hole transport capability of the p-type carbazole group, which is detrimental to carrier balance. In contrast, the carbazole groups in compounds DBH2-DBH5 are not deuterated, therefore their μh / μe ratios are slightly higher than those of the compounds provided in this invention. In contrast, the carbazole groups in compounds DBH1 and DBH6 are fully deuterated, resulting in higher μh / μe values. This indicates that hole mobility is significantly higher than electron mobility, leading to an imbalance between hole and electron mobility. It also shows that deuterated carbazole enhances the hole transport capability of the p-type carbazole group, which is detrimental to carrier balance. Compared to compound BH8 provided in this invention, the carbazole groups in compounds DBH7 and DBH8 are partially deuterated, which is also detrimental to carrier balance.
[0100] Regarding the average intermolecular distance of R_BH molecules: Hole mobility is affected not only by deuteration but also by the intermolecular distance. Although the carbazole in the comparative compound DBH2-DBH5 is not deuterated, its hole mobility is still faster than that of the embodiment provided in this invention. This is because the carbazole and anthracene in the comparative compound DBH2-DBH5 are located at the para position of benzene, resulting in left-right symmetry of the entire molecule. This facilitates intermolecular face-to-face stacking, leading to short intermolecular distances, which is beneficial for the "jumping" transport of holes between molecules. In contrast, the compound provided in this invention contains sterically hindered groups or is coupled to specific sterically hindered sites, resulting in larger intermolecular distances and relatively slower hole mobility, thus promoting carrier balance.
[0101] Composition performance evaluation 1. Intermolecular distance R_BHA (Å): Using Gromacs 2019.3 software, a 10*10*10nm cubic box was constructed based on the GAFF force field and RESP atomic charge. The ratio of the first luminescent material to the second luminescent material was 1:1. The host and guest molecules were randomly placed into the box using the conjugate gradient method, minimizing energy to eliminate the repulsive force caused by unreasonable intermolecular arrangement in the system. Then, a 100ps equilibrium molecular molecular MD simulation was performed under NVT to achieve complete system equilibrium. Based on this system, a 5ns generation MD simulation was performed using NPT with periodic boundary conditions under an external environment setting of 1 atm and 298K. The MD trajectory of the last 2ns was divided into 20 parts, and the average intermolecular distance (R_BHA) between the two first luminescent materials in this invention was calculated. The results are shown in Table 4.
[0102] The host and guest molecular structures used in the MD simulations were obtained using Gaussian 16 C.01 software, based on density functional theory (DFT) calculations (basis set level set to b3lyp / 6-31G(d), charge number 0), through geometric optimization and vibrational analysis (Opt+freq). During the calculations, none of the structures used had imaginary frequencies.
[0103] 2. Mobility: To demonstrate that the composition provided by the present invention can balance carrier transport, the hole mobility μh and electron mobility μe of the compositions in Tables 1 and 2 were measured, and then μh / μe was calculated. The closer the value of μh / μe is to 1, the more balanced the carrier transport in the composition is. The larger the value, the stronger the hole transport capability.
[0104] Specific experimental steps: The compositions of the present invention, T1-T6 and comparative examples DT1-DT4, were deposited on ITO to form a 1000 nm thin film, and then (Al) was deposited on the thin film to form a cathode with a thickness of 150 nm to obtain the sample to be tested. A deflection voltage of 20 volts was applied to the sample to be tested. The hole mobility μh and electron mobility μe of the material were calculated by measuring the time it took for the photogenerated carriers of the sample to pass through the sample under the applied electric field. The μh / μe ratio was then calculated. The closer the μh / μe ratio is to 1, the more balanced the carrier transport is. The specific calculation results are shown in Table 4.
[0105] Table 4
[0106] As can be seen from the table above, the composition provided by the present invention has a suitable intermolecular spacing and a relatively balanced carrier transport.
[0107] In contrast, BH8 in control 1, which contains only a single P-type, has a shorter intermolecular distance, resulting in faster hole transport. Excess holes are more likely to form a polaron-exciton quenching effect, leading to a decrease in exciton radiative transition efficiency.
[0108] Control 2 contains only N-type BHB1, which also has a short intermolecular distance, similar to Control 1. However, carrier transport is dominated by electrons, and the carriers are also unbalanced.
[0109] The second luminescent material in the composition DT1-DT4 contains a large sterically hindered segment (anthracene nucleus flanking group with more than 20 carbon atoms), which further increases the intermolecular distance between the first luminescent materials, further reducing hole transport, even below the electron transport rate, resulting in excess electron quenching of excitons and reducing the effective utilization rate of excitons.
[0110] OLED manufacturing and characterization Device Examples The organic electroluminescent device provided by the present invention includes an anode, a hole transport region, a light-emitting layer, an electron transport region, and a cathode sequentially disposed on a substrate. Furthermore, the hole transport region includes a hole injection layer, a hole transport layer, and a light-emitting auxiliary layer; the electron transport region includes an electron transport layer and an electron injection layer.
[0111] Furthermore, the light-emitting layer is composed of a host material and a guest material, and the host material of the light-emitting layer can be composed of one molecular material or multiple molecular materials.
[0112] The compounds and compositions described in this invention can be used in the light-emitting layer of the aforementioned organic electroluminescent devices.
[0113] In this embodiment, the anode uses a commonly used anode material in the art, such as ITO, Ag, or their multilayer structures. The hole injection layer uses a commonly used hole injection material in the art, with F4TCNQ, HATCN, NDP-9, etc., added for doping. The hole transport layer uses a commonly used hole transport material in the art. The light-emitting layer uses the host and guest material composition provided by this invention. The electron transport layer uses a commonly used electron transport material in the art. The electron injection layer uses a commonly used electron injection material in the art, such as LiQ, LiF, Yb, etc. The cathode uses a commonly used material in the art, such as metallic Al, Ag, or metal mixtures (Ag-doped Mg, Ag-doped Ca, etc.).
[0114] The electrode fabrication method and the deposition method of each functional layer in this embodiment are conventional methods in the art, such as vacuum thermal evaporation or inkjet printing, and will not be described in detail here. Only some process details and testing methods in the fabrication process are supplemented as follows: Device Example 1 The substrates used in this invention are all subjected to the following operations: ITO / Ag / ITO substrates are patterned to have a light-emitting area of 3mm × 3mm, then subjected to ultrasonic treatment with water / isopropanol, UV / ozone irradiation, and then dried at 100°C. Afterwards, the ITO substrates are mounted on the substrate support of a vacuum deposition apparatus, and the pressure is adjusted to achieve a vacuum rate of 1 × 10⁻⁶. -7torr. Then, the following operations are performed: First, a hole injection layer is formed on the ITO layer (anode) formed on the substrate by vacuum deposition of compounds HT01 and PD01 (mass ratio of HT01 to PD01 is 97:3) with a thickness of 10 nm; second, a hole transport layer is formed on the hole injection layer by vacuum deposition of compound HT01 with a thickness of 100 nm; next, a light-emitting auxiliary layer is formed on the hole transport layer by vacuum deposition of compound BP01 with a thickness of 5 nm; next, a light-emitting layer is formed on the light-emitting auxiliary layer by vacuum deposition of a mixture of compounds BH1 and BD01 provided by the present invention with a thickness of 20 nm, wherein compound BH1 is used as the host material and compound BD01 is used as the guest material, with a mass ratio of host material to guest material of 98:2; then, a hole blocking layer is formed on the light-emitting layer by vacuum deposition of compound HB01 with a thickness of 5 nm; then… Subsequently, on the aforementioned hole-blocking layer, a 30 nm thick layer of compound ET01 and compound LiQ (with a mass ratio of 1:1) was vacuum-deposited to form an electron transport layer. Then, on the electron transport layer, a 1 nm thick layer of Yb was vacuum-deposited to form an electron injection layer. Next, on the electron injection layer, a 15 nm thick layer of Mg and Ag (with a mass ratio of 1:9) was deposited to form a cathode. Then, on the cathode, a 50 nm thick layer of compound CP01 was deposited to form a capping layer. Finally, the vapor-deposited substrate was encapsulated. A UV adhesive coating process was used to coat the cleaned cover plate. The coated cover plate was then moved to the lamination section, and the vapor-deposited substrate was placed on top of the cover plate. Finally, the substrate and cover plate were laminated using a bonding device, while simultaneously curing the UV adhesive under light. This process fabricated a top-emitting organic light-emitting device. The device structure is described in [reference needed]. Figure 1 .
[0115] Apart from the host and guest materials of the luminescent layer, the molecular structural formulas of the other layers are as follows:
[0116] .
[0117] Device Examples 2-15 Organic electroluminescent devices were fabricated using the compounds described in the other examples in Table 5 using the above method. Specifically, blue organic electroluminescent devices Examples 2-15 were fabricated by replacing BH1 in Device Example 1 with the main material shown in the examples in Table 5.
[0118] Device Comparison Examples 1-8 Organic electroluminescent devices were prepared by using the above method to replace the BH1 in the comparative examples in Table 5. Specifically, blue organic electroluminescent devices (Comparative Examples 1-8) were prepared by replacing the main material shown in the comparative examples in Table 5 with the main material shown in the comparative examples in Device Example 1.
[0119] The OLED devices described above were tested using standard methods. For this purpose, J = 10 mA / cm² was used. 2 The driving voltage and luminous efficiency of the organic electroluminescent device were determined under a specific current density. The lifetime LT was defined as the time after which, when operating at a constant current J, the brightness decreased from the initial luminous brightness L0 to a specific proportion L1; J = 50 mA / cm². 2 The statement L1 = 90% refers to a value of 50 mA / cm. 2 When operating below the threshold, the luminous intensity decreases to 90% of its initial value L0 after time LT. Similarly, J = 20 mA / cm² 2 L1 = 80% means that at 20 mA / cm 2 When operating below a certain threshold, the luminous intensity decreases to 80% of its initial value L0 after time LT. This test used LT95, which refers to the blue light-emitting device at J=20mA / cm². 2 When operating below, the luminous intensity drops to 95% of its initial value L0 after time LT95.
[0120] The testing instruments and methods used to perform performance testing on the OLED devices of the above embodiments and comparative examples are as follows: Luminous efficacy (CE) (cd / A) and chromaticity coordinates (CIEy) were measured using a PhotoResearch PR-655 spectral scanner. Current density and turn-on voltage: tested using a Keithley 2400 digital source meter; The luminous efficiency of blue light devices is greatly affected by chromaticity. The industry generally uses the BI value as the basis for the efficiency of blue light devices. BI (Blue index) is obtained by dividing the luminous efficiency CE (cd / A) by the chromaticity coordinate (CIEy). Lifetime testing: Using a silicon photonics-based OLED device lifetime testing system.
[0121] The performance test results of the above devices are listed in Table 5.
[0122] Table 5
[0123] As can be seen from the above device evaluation results, compared with the comparative device, the device embodiment provided by this invention has significant advantages in both lifetime and efficiency (EQE and LT95 are both greater than those of the comparative device). This is because this invention reduces the degree of molecular photodegradation through local deuteration, coordinates carrier balance, improves exciton recombination and utilization, improves energy transfer efficiency, and enhances EQE and device lifetime.
[0124] Among the devices in Comparative Example 6, compound DBH6 exhibited the highest deuteration rate and the lowest photodegradation, resulting in the longest device lifetime. However, deuteration also had the greatest impact on hole transport, leading to a highly unbalanced carrier state, severe polaron-exciton quenching, significant efficiency roll-off, and reduced EQE.
[0125] In Comparative Examples 1, 7, and 8, the anthracene or the flanking groups of the main material were not deuterated, and the carbazole groups were fully or partially deuterated. This resulted in the inability to effectively avoid photodegradation impurities and further imbalance of charge carriers, thus leading to low EQE and short lifetime of the devices.
[0126] In Comparative Examples 2-5, the anthracene and its flanking groups were not deuterated simultaneously, resulting in photodegradation impurities and reduced lifetime. At the same time, the degradation impurities also acted as exciton traps, slightly affecting exciton radiative transitions and causing a slight decrease in EQE.
[0127] Device Example 16 This example provides an organic electroluminescent device, the fabrication method of which is as follows: First, a hole injection layer is formed on an ITO layer (anode) formed on a substrate by vacuum deposition of compound HTL and compound F4TCNQ (mass ratio of compound HTL to compound F4TCNQ is 97:3) with a thickness of 10 nm; second, a hole transport layer is formed on the hole injection layer by vacuum deposition of compound HTL with a thickness of 120 nm; third, a light-emitting layer is formed on the hole transport layer by vacuum deposition of a mixture of premixed composition T1 and compound BD with a thickness of 40 nm, wherein composition T1... As the host material, the formulation of composition T1 is prepared according to Table 1, and compound BD is used as the guest material. The mass ratio of host material to guest material is 97:3. Then, on the above-mentioned light-emitting layer, compound ET-01 and compound LiQ (mass ratio of ET-01 to LiQ is 1:1) are vacuum deposited to a thickness of 35 nm to form an electron transport layer. Then, on the above-mentioned electron transport layer, LiF is deposited to a thickness of 0.2 nm to form an electron injection layer. Finally, on the above-mentioned electron injection layer, aluminum (Al) is deposited to a thickness of 150 nm to form a cathode, thus preparing an organic electroluminescent device.
[0128] Apart from the main material of the light-emitting layer, the molecular structural formulas of the other layers are as follows: .
[0129] Device Examples 17-21 The preparation method is the same as that in Device Example 16, except that the main material is replaced according to Table 6.
[0130] Device Comparison Examples 9-14 The preparation method is the same as that of device example 16, except that the main material described in the device comparative examples in Table 6 is replaced with the main material in device example 16 to prepare an organic electroluminescent device.
[0131] The organic electroluminescent devices provided in Device Examples 16-21 and Device Comparative Examples 9-14 were tested using standard methods. For this purpose, J = 10 mA / cm² was used. 2 The driving voltage, luminance, electroluminescent current efficiency (in cd / A), and external quantum efficiency (EQE, in percentage) of the organic electroluminescent device were determined at a given current density. These were calculated as a function of luminescence density from the current / voltage / luminescence density characteristic line (IVL characteristic line), which exhibits Lambertian emission characteristics, and the emission spectrum. The lifetime LT was defined as the time after which, when operating at a constant current J, the luminance decreased from the initial luminance L0 to a specific proportion L1; J = 50 mA / cm². 2 The statement L1 = 90% refers to a value of 50 mA / cm. 2 When operating below the threshold, the luminous intensity decreases to 90% of its initial value L0 after time LT. Similarly, J = 20 mA / cm² 2 L1 = 80% means that at 20 mA / cm 2 When operating below a certain threshold, the luminous intensity decreases to 80% of its initial value L0 after time LT. This test used LT95, which refers to the blue light-emitting device at J=20mA / cm². 2 When operating below, the luminous intensity drops to 95% of its initial value L0 after time LT95.
[0132] The testing instruments and methods used to perform performance testing on the above-mentioned OLED devices are as follows: Brightness was tested using a PhotoResearch PR-655 spectral scanner; Current density and turn-on voltage: tested using a Keithley 2400 digital source meter; Life test: The LT-96ch life test device was used.
[0133] The performance test results of the above devices are listed in Table 6.
[0134] Table 6
[0135] In the device examples 16-21, the second compound contained in the main material is a pure aromatic hydrocarbon compound. By utilizing the intermolecular distance and its own transport characteristics, the carrier transport balance of the light-emitting layer is adjusted, the exciton recombination probability and effective utilization are improved, the EQE is improved, and the efficiency roll-off and device lifetime can be effectively avoided.
[0136] Comparative examples 9 and 10 show that the main material contains only one compound, which leads to the carrier transport being dominated by holes or electrons. This easily leads to polaron-exciton aggregation-induced quenching, reducing the exciton recombination probability and thus weakening the light extraction efficiency of the device, resulting in a decrease in EQE.
[0137] In the device comparative examples 11-14, the second compound contained in the host material contains large position groups, which leads to a significant decrease in hole transport capability, a slower and unbalanced carrier transport rate, and excitons are prone to aggregate and quench with polarons, resulting in relatively low EQE and lifetime.
[0138] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the implementation of the present invention. For those skilled in the art, other variations or modifications can be made based on the above description. It is impossible to exhaustively list all the implementation methods here. All obvious variations or modifications derived from the technical solutions of the present invention are still within the protection scope of the present invention.
Claims
1. A first luminescent material, characterized in that, The structure of the first luminescent material is shown below: 。 2. A luminescent material composition, characterized in that, The luminescent material composition includes the first luminescent material as described in claim 1 and the second luminescent material with a general structural formula as shown in Formula II; II; Wherein, X represents any one of substituted or unsubstituted phenyl, substituted or unsubstituted naphthyl, substituted or unsubstituted phenanthryl, or substituted or unsubstituted pyrene, and when X contains a substituent, the substituent is selected from phenyl or naphthyl. Y represents any one of phenyl, biphenyl, terphenyl, or naphthyl; In Formula II, any one of the hydrogen atoms can be replaced by deuterium.
3. The luminescent material composition according to claim 2, characterized in that, The second luminescent material is selected from the structure shown below: 。 4. The use of the first luminescent material as described in claim 1 or the luminescent material composition as described in any one of claims 2 to 3 in the preparation of organic electroluminescent devices.
5. An organic electroluminescent device, characterized in that, It includes an anode, a hole transport region, a light-emitting layer, an electron transport region, and a cathode sequentially disposed on a substrate; wherein the light-emitting layer includes the first light-emitting material as described in claim 1.
6. An organic electroluminescent device, characterized in that, It includes an anode, a hole transport region, a light-emitting layer, an electron transport region, and a cathode sequentially disposed on a substrate; wherein the light-emitting layer comprises the light-emitting material composition according to any one of claims 2 to 3.
Citation Information
Patent Citations
Organic compound and organic electroluminescent element comprising the same
CN110776392A
Composite host material, organic electroluminescent layer material and application thereof, and organic electroluminescent device
CN121717750A
An electroluminescent compound and an electroluminescent device comprising the same
KR1020160123508A